Self-Persuasion: Evidence from Field Experiments at International Debating Competitions - Schwardmann, Peter; Tripodi, Egon; van der Weele, Joël J. (American Economic Review, 2022)
Laboratory evidence shows that when people have to argue for a given position, they persuade themselves about the position’s factual and moral superiority. Such self-persuasion limits the potential of communication to resolve conflict and reduce polarization. We test for this phenomenon in a field setting, at international debating competitions that randomly assign experienced and motivated debaters to argue one side of a topical motion. We find self-persuasion in factual beliefs and confidence in one’s position. Effect sizes are smaller than in the laboratory, but robust to a one-hour exchange of arguments and a tenfold increase in incentives for accuracy. (JEL C93, D12, D72, D83, D91, I23)